L’open innovation nel contesto delle PMI vitivinicole - Presenza, Angelo (Piccola Impresa / Small Business, 2015)
The study aims to deepen knowledge on the Open Innovation (OI) approach. The focus is on how Wine SMEs organize themselves to sustain OI and to answer the matters that influence in opening/closing the approach to innovation. The work performs an explorative qualitative analysis using the multiple case-study methodology with ten Italian wine firms. Although this firms present an increasing interest in actions related to OI, the findings show that so far it has not put in place a real declared strategy. The study highlights several barriers that hinder the adoption of OI model: cultural and organizational differences among involved partners; lack of knowledge, resources and competencies. The findings suggest that open innovation is a field of increasing interest for both academics and practitioners and we cannot yet speak of a veritable declared strategy. It appears more like a set of fragmented initiatives and, moreover, at a beginning stage with several barriers that hinder a significant improvement.